Poster sessions as an authentic assessment approach in an open-Ended University general chemistry laboratory - Dogan, Alev; Kaya, Osman Nafiz (Elsevier Science Bv, 2009)
The purpose of this study is to explore the views of Pre-service Science Teachers (PSTs) on their posters as an authentic assessment tool in an open-ended chemistry laboratory course. Forty-three PSTs set up their research questions, designed and performed laboratory investigations, obtained results of their experiments and prepared their posters as an alternative to traditional laboratory reports. They engaged in the process of assessment in the course as both self and peer evaluators. At the end of each laboratory session, each group of the PSTs presented posters of their laboratory investigations to their peers and instructors. Results of the PSTs' interview analyses indicated that most PSTs expressed many benefits to the presentation of laboratory investigations using posters in comparison to the traditional laboratory reports. (C) 2009 Elsevier Ltd. All rights reserved
World Conference on Educational Sciences -- FEB 04-07, 2009 -- Nicosia, CYPRUS
Keywords: Pre-service teachers; science teacher education; science laboratory; authentic assessment; poster session